2015
DOI: 10.1515/dx-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the preferential use of disease prototypes over case exemplars among early year one medical students prior to and following diagnostic training

Abstract: Background: Two core dual processing theory (DPT) System I constructs (Exemplars and Prototypes) were used to: 1) formulate a training exercise designed to improve diagnostic performance in year one medical students, and 2) explore whether any observed performance improvements were associated with preferential use of exemplars or prototypes. Methods: With IRB approval, 117 year one medical students participated in an acute chest pain diagnostic training exercise. A pre-and post-training test containing the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Research at UNTHSC/TCOM involving computer-based, dual processing theory-driven approaches to DD training has demonstrated that first-and secondyear students and practicing physicians achieve improved DD accuracy. [14][15][16] Two additional semesters of AME coursework and II processing mechanisms involving pattern recognition and rule-based constructs) during case-based practice opportunities conducted in a small group, faculty-facilitated learning environment. The AME faculty now have the opportunity and challenge to organize and produce institutional review board-approved research protocols to determine whether these innovations are leading to improved DD performance.…”
Section: Resultsmentioning
confidence: 99%
“…Research at UNTHSC/TCOM involving computer-based, dual processing theory-driven approaches to DD training has demonstrated that first-and secondyear students and practicing physicians achieve improved DD accuracy. [14][15][16] Two additional semesters of AME coursework and II processing mechanisms involving pattern recognition and rule-based constructs) during case-based practice opportunities conducted in a small group, faculty-facilitated learning environment. The AME faculty now have the opportunity and challenge to organize and produce institutional review board-approved research protocols to determine whether these innovations are leading to improved DD performance.…”
Section: Resultsmentioning
confidence: 99%
“…One of the authors (BH) designed the survey and distributed it to 254 health related professionals while they were attending university courses or seminars at the Faculty of Medicine, University of Oslo, during the spring terms of 2010 to 2014. The respondents were categorized as MD (42), RN (67), physiotherapists (22), psychologists (13), and others (52). The latter category encompassed dentists, biologists, epidemiologists, social scientists, philosophers, and professionals with backgrounds from other humanities.…”
Section: Methodsmentioning
confidence: 99%
“…Learning researchers have highlighted that dual processing theories are adequate references to understand the basic structures of knowledge and intellectual abilities, 3 because they recognize the existence of analytical and non-analytical processes. Considering the evidence that diagnostic reasoning in nursing uses and should use both processes, it has become a logical selection to adopt a dual processing theory as the theoretical framework to guide the methodology construction.…”
Section: Theories and Concepts For The Methodology To Construct Simulmentioning
confidence: 99%
“…11 Dual processing theories are important for diagnostic reasoning in nursing, because diagnoses represent a category of phenomena that have a poorly defined nature, allowing the two processing systems to act concomitantly. 3,7 Indeed, nursing diagnoses have aspects that define them as poorly-defined phenomena/concepts, as follows: have few reference standards; need defining characteristics that would be the diagnostic criteria; and be linked with different concepts that are not synonyms, but are often used by some as if they were, such as human response, problem, need, among others.…”
Section: Theories and Concepts For The Methodology To Construct Simulmentioning
confidence: 99%
See 1 more Smart Citation